Essential Oils in Limiting the Development of Various Origins of Phytopathogenic Fusarium Isolates from Wheat Kernels - Krzysko-Lupicka, Teresa; Sporek, Monika (Innovations in Microbiology and Biotechnology Vol. 6, 2022)
The aim of the study was to determine the relationship between the chemical composition of eight commercial essential oils (EsO) (grapefruit, lemongrass, tea tree (TTO), thyme, verbena, cajeput, Litsea cubeba and garlic) and their fungistatic activity in relation to four species of Fusarium from the Polish population (F. avenaceum FAPL, F. culmorum FCPL, F. graminearum FGPL and F. oxysporum FOPL) and five from the German population (F. culmorum FC1D, F. culmorum FC2D, F. graminearum FG1D, F. graminearum FG2D and F. poae FP0D). In addition, the identification of EsO as potential biofungicides. Phytopathogenic fungi obtained from infected wheat kernels. The species identification of Fusarium isolates was confirmed by matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometer. The determination of qualitative and quantitative chemical composition of the EsO was carried out using the gas chromatography–mass spectrometry (GC–MS) method. The disc plate method was used to investigate the fungicidal activity of EsO (at doses of 0.025; 0.05; 0.125; 0.25; 0.50; 1.0, and 2.0 percent) against Fusarium spp. and zones of growth inhibition were measured. Essential oils (as potential biofungicides) were found to successfully limit the development of Fusarium spp. based on the results presented as a growth rate index. German Fusarium isolates were usually more sensitive than those from the Polish population. Individual Fusarium species had varying degrees of susceptibility. Their vulnerability, regardless of the isolate origin, in order from the most to the least sensitive, is as follows: F. culmorum, F. graminearum, F. poae, F. avenaceum and F. oxysporum. The strongest fungicidal activity, similar to Funaben T, showed thymol chemotype oil (regardless of the concentration). Performance of citral oils (lemongrass and Litsea cubeba) was similar, but in concentration above 0.025%. Garlic and grapefruit oils were the least effective.